Bibliometric Analysis: Digital Comics as a Learning Resource to Improve the Learning Effectiveness of Elementary School Students - Norkhalizah, Norkhalizah; Mansur, Hamsi; Rini, Sulistyo (Jurnal Evaluasi dan Pembelajaran, 2025)
This study aims to analyze trends and research correlations regarding the use of digital comics as a learning resource to enhance elementary school students' learning effectiveness in the IPAS subject (Integrated Natural and Social Sciences) over the past five years. The method used is a literature study with bibliometric analysis utilizing VOSviewer software. A total of 200 journals from various academic sources were analyzed to identify patterns of keyword relationships, research trends, and scientific gaps that have not been widely explored. The results show that there are three main clusters in the study of digital comics as learning resources: learning effectiveness, the role of teachers and learning media, and the development of innovative learning resources. Network visualization using VOSviewer reveals that digital comics contribute to increasing student engagement, clarifying conceptual material, and assisting teachers in delivering more interactive lessons. Based on these findings, it is recommended that future research focus on developing more adaptive digital comic-based learning models and integrating interactive technology to improve learning effectiveness in elementary schools.